2009
DOI: 10.1002/jrs.2528
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermostability and phonon–phonon interactions in Mo6S3I6 nanowires by Raman scattering spectroscopy

Abstract: Detailed Raman scattering measurements were performed on molybdenum-sulfur-iodine nanowires (Mo 6 S 3 I 6 ). At room temperature, 21 well-resolved Raman modes were experimentally observed for the first time in this new compound. The phase stability and vibrational properties of the nanowires were investigated by different temperature treatments. High-temperature Raman spectra showed that the phase separation of Mo 6 S 3 I 6 nanowires took place between 573 and 673 K, followed by appearance of a new mode at 819… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Raman modes observed in spectra of nonactivated sample were assigned to Raman spectra of the ZnO monocrystal, while the spectra of mechanically activated samples point to structural and stoichiometric changes, depending on the milling time and the choice of equipment. Detailed Raman scattering measurements were performed on molybdenum–sulfur–iodine NWs (Mo 6 S 3 I 6 ) by Todorovic et al ., where at room temperature, 21 well‐resolved Raman modes were experimentally observed for the first time in this new compound . Raman scattering spectra showed a significant difference in phonon–phonon interactions between internal and external Raman modes of the Mo 6 S 3 I 6 NWs.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…Raman modes observed in spectra of nonactivated sample were assigned to Raman spectra of the ZnO monocrystal, while the spectra of mechanically activated samples point to structural and stoichiometric changes, depending on the milling time and the choice of equipment. Detailed Raman scattering measurements were performed on molybdenum–sulfur–iodine NWs (Mo 6 S 3 I 6 ) by Todorovic et al ., where at room temperature, 21 well‐resolved Raman modes were experimentally observed for the first time in this new compound . Raman scattering spectra showed a significant difference in phonon–phonon interactions between internal and external Raman modes of the Mo 6 S 3 I 6 NWs.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…Further, in the Mo 6 S 8 CP, Mo-torsional mode (below 175 cm −1 : external mode generated by Mo−Mo vibration) and S-breathing mode (above 200 cm −1 : internal mode showing S−S breathing vibration) are indicated in each of the two regions by Raman of S8. 37,38 When magnesium is inserted into the CP, it can be confirmed that the vibration is strong in the 24 and 48 h data due to the weak van der Waals bond with the sulfur atom. In general, (1)…”
Section: Mg Insertion In Mo 6 S 8 Cpmentioning
confidence: 87%
“…When Mg ions are inserted, they are smaller than Cu ions (if we compare the Mg−Mg and Cu−Cu distances ∼1.93 and 2.24 Å, respectively) and exist as polyhedra in cavities 1 and 2. 37,38 These explanations point out the difference in Mg insertion in CPs with the same rhombohedral structure. As shown in XRD (Figure 6c), more Mg ions insert the cavity in the triclinic structure of 48 h. It has been reported that the triclinic distortion of selenide (Mo 6 Se 8 ) Mg insertion changes the geometry of the cation sites and leads to the high Mg mobility in the whole intercalation range.…”
Section: Mg Insertion In Mo 6 S 8 Cpmentioning
confidence: 99%
“…First, we confirmed the wire growth by SEM (figure 3(a)), and nanowires seem to be highly dense, and the Mo 6 S 3 I 6 NWs and MoS 2 were synthesized at 900 °C. Above 1000 °C, the torsional mode of Mo as Mo6 octahedron can be observed at 94.27 cm -1 in figure 3(c) [18][19][20][21][22]. In addition, at 1000 °C, the crystallinity of Mo 6 S 3 I 6 NWs were improved and characterized by XRD, SEM, and Raman spectroscopy.…”
Section: Analysis Of Mo 6 S 3 I 6 Nanowirementioning
confidence: 93%
“…In addition, at 1000 °C, the crystallinity of Mo 6 S 3 I 6 NWs were improved and characterized by XRD, SEM, and Raman spectroscopy. MoS 2 and Mo 2 S 3 phases were observed at 2θ=14.44 (MoS 2 , ICCD number: 98-002-6622) and 2θ=16.24 (Mo 2 S 3 , ICCD number: 01-081-2031), respectively, in XRD, [18,19] and 310, 378, and 407 cm -1 in Raman spectroscopy [18,20]. At 1050 °C, the MoS 2 disappeared, the nanowire crystallinity improved, and the Mo 6 S 6 I 2 phase acting as a Mo 6 S 3 I 6 NW seed was observed.…”
Section: Analysis Of Mo 6 S 3 I 6 Nanowirementioning
confidence: 97%